2022
DOI: 10.1186/s12888-022-04311-5
|View full text |Cite|
|
Sign up to set email alerts
|

Associations of impulsivity, hyperactivity, and inattention with nonsuicidal self-injury and suicidal behavior: longitudinal cohort study following children at risk for neurodevelopmental disorders into mid-adolescence

Abstract: Background The knowledge of how the separate Attention-Deficit/Hyperactivity Disorder (ADHD) subdimensions (impulsivity, hyperactivity, and inattention) are associated with nonsuicidal self-injury (NSSI) and suicidal behavior (SB) is limited. The objective of this study was to investigate the associations of childhood ADHD subdimensions with NSSI and SB in children at risk of neurodevelopmental disorders (NDDs; including ADHD). Methods The sample (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…This is consistent with the discovery that inattention was associated with NSSI in childhood and adolescence. 48 Concentration difficulties are present in many mental disorders, such as anxiety disorder 49 and eating disorder, 50 which are commonly comorbid with NSSI. 51 , 52 In our study, concentration was assessed by one of the items on the PHQ-9 (Trouble concentrating on things, such as reading the newspaper or watching television), which was more subjective.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with the discovery that inattention was associated with NSSI in childhood and adolescence. 48 Concentration difficulties are present in many mental disorders, such as anxiety disorder 49 and eating disorder, 50 which are commonly comorbid with NSSI. 51 , 52 In our study, concentration was assessed by one of the items on the PHQ-9 (Trouble concentrating on things, such as reading the newspaper or watching television), which was more subjective.…”
Section: Discussionmentioning
confidence: 99%
“…The percentage affecting the gingiva was only 4.60%. Mounting evidence indicates that children and adolescents with attention deficit and hyperactivity disorder (ADHD) or subsyndromal ADHD have a significantly increased risk of self-inflicted injury [ 23 25 ]. A previous study also found that self-mutilation of the oral cavity is very common in mentally retarded children [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Even in the last month, highly behavioral impulsivity was less likely to make deliberate attempts ( 46 ). However, another longitudinal cohort study of children at risk for neurodevelopmental disorders in mid-adolescence suggested that impulsivity and inattention may be particularly important in understanding the onset of NSSI and suicidal behaviors ( 54 ). Specifically, adolescents are in the developmental stage of self-cognitive ability whose self-reported results vary significantly.…”
Section: Discussionmentioning
confidence: 99%